Light‐Controllable Ionic Conductivity in a Polymeric Ionic Liquid. (4th February 2020) - Nie, Hui; Schauser, Nicole S.; Dolinski, Neil D.; Hu, Jerry; Hawker, Craig J.; Segalman, Rachel A.; Read de Alaniz, Javier
Abstract: Polymeric ionic liquids (PILs) have attracted considerable attention as electrolytes with high stability and mechanical durability. Light‐responsive materials are enabling for a variety of future technologies owing to their remote and noninvasive manipulation, spatiotemporal control, and low environmental impact. To address this potential, responsive PIL materials based on diarylethene units were designed to undergo light‐mediated conductivity changes. Key to this modulation is tuning of the cationic character of the imidazolium bridging unit upon photoswitching. Irradiation of these materials with UV light triggers a circa 70 % drop in conductivity in the solid state that can be recovered upon subsequent irradiation with visible light. This light‐responsive ionic conductivity enables spatiotemporal and reversible patterning of PIL films using light. This modulation of ionic conductivity allows for the development of light‐controlled electrical circuits and wearable photodetectors. Abstract : Polymere ionische Flüssigkeiten (PILs) auf Basis von Diarylethen wurden entwickelt, die unter Lichteinwirkung ihre Leitfähigkeit ändern. Entscheidend für diese Modulation ist die Änderung des kationischen Charakters der Imidazolium‐Brückeneinheit beim Photoschalten. Bestrahlung mit UV‐Licht löst einen 70 %igen Abfall der Leitfähigkeit im Festkörper aus, die sich bei Bestrahlung mit sichtbarem Licht wiederherstellen lässt.